Effectiveness of Telemedicine in Managing Mental Health Disorders in Kenya - Cheroo, Dr. Andrian (American Journal of Health, Medicine and Nursing Practice, 2024)
Purpose: The aim of the study was to assess the effectiveness of telemedicine in managing mental health disorders in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Study indicated that telemedicine interventions, including virtual therapy sessions and remote monitoring, have been instrumental in improving patient outcomes. Patients report increased convenience, reduced wait times for appointments, and greater flexibility in scheduling sessions, which enhances overall engagement with treatment plans. Moreover, telemedicine has demonstrated efficacy across various mental health conditions, including anxiety disorders, depression, and post-traumatic stress disorder (PTSD). Studies have shown comparable clinical outcomes between telemedicine and face-to-face interventions, with some indicating potential advantages such as higher patient satisfaction and lower dropout rates. However, challenges remain, such as ensuring privacy and data security, as well as addressing technological barriers for marginalized populations. Continued study and policy developments are crucial to optimizing telemedicine's role in mental health care, aiming to integrate these innovative approaches into mainstream practice effectively. Implications to Theory, Practice and Policy: Social cognitive theory (SCT), technology acceptance model and health belief model may be used to anchor future studies on assessing the effectiveness of telemedicine in managing mental health disorders in Kenya. In terms of practice, it is crucial to develop evidence-based guidelines and best practices for the implementation of telemedicine interventions in mental health care. Advocating for policy changes and reimbursement mechanisms that support the widespread adoption and sustainability of telemedicine in mental health care is crucial.